2020
DOI: 10.1088/1742-6596/1511/1/012041
|View full text |Cite
|
Sign up to set email alerts
|

Teacher readiness in accommodating the TPACK framework to meet teacher competence the 21st Century

Abstract: One of the advantages of digital technology (internet) as the 21st century characterizes learning is the availability and accessibility of teaching materials. The purpose of the study was to formulate specific competencies and measure the readiness of teachers to face 21st-century learning. Based on four teachers’ competencies and three TPACK components, it has been defined as a specific competency attribute for 21st-century teacher competences. The research phase begins with the FGD process and concludes with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 1 publication
0
4
0
1
Order By: Relevance
“…All these studies are clustered among TPACK and the technological competency of teachers. Interestingly, while many studies mentioned that teachers have low technological competency, Sarwa et al (2020) reported that the North Sumatera teachers were ready to face 21st-century learning situations, though it was not mentioned which 21st-century learning skill was focused on. Another interesting discovery was disclosed by Jwaifell et al (2018), where it was noted that female teachers' readiness to use technology was higher than their male counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…All these studies are clustered among TPACK and the technological competency of teachers. Interestingly, while many studies mentioned that teachers have low technological competency, Sarwa et al (2020) reported that the North Sumatera teachers were ready to face 21st-century learning situations, though it was not mentioned which 21st-century learning skill was focused on. Another interesting discovery was disclosed by Jwaifell et al (2018), where it was noted that female teachers' readiness to use technology was higher than their male counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…Malahan, kajian Sarwa et al (2020) mendapati masih terdapat guru yang berada dalam keraguan (19.6%) dan 6.4% guru tidak bersedia untuk menerapkan PTPIK bagi memenuhi kompetensi guru pada abad ke-21. Tiba dan Condy ( 2021) pula menyimpulkan bengkel-bengkel yang diadakan oleh pihak fakulti adalah tidak mencukupi untuk mempersiapkan guru pelatih untuk mengajar menggunakan teknologi.…”
Section: Sorotan Literaturunclassified
“…Many recent studies have raised issues related to TPACK-starting with research on teachers' readiness to use technology in learning, such as research by Jwaifell et al (2018), which aims to investigate teacher readiness to teach within the TPACK framework. A study by Simaremare et al (2020) determines the components in TPACK as specific competencies for 21st-century teacher competencies. The research results show that teachers in North Sumatra accept and are ready for 21st-century learning.…”
Section: Introductionmentioning
confidence: 99%